2008
DOI: 10.4321/s0211-95362008000100013
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of tropical medicine in Portugal: The School of Tropical Medicine and the Colonial Hospital of Lisbon (1902-1935)

Abstract: The School of Tropical Medicine was founded in 1902 along with the Colonial Hospital of Lisbon. The Portuguese government recognized the importance of colonising the tropics and therefore supported the creation of a specific locus of medical training that would prove to be crucial to the clinical and experimental study of tropical diseases. This paper examines the importance of such institutions for the emergence of a new scientific area of research while also functioning as a consolidation factor for the Thir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 1 publication
0
10
0
4
Order By: Relevance
“…The report concluded that the disease was only "lightly endemic" and "apparently benign," with "irregular dissemination across the territory" (Sequeira, 1935a, p.11). It took into account the previous experiences of teams sent by the Escola de Medicina Tropical to study, locate and eradicate trypanosome on the island of Príncipe, where programs had been implemented between 1904and 1913(Amaral, 2008, and later in (Northern) Angola. The fact that the same author published a similar contribution in French illustrates the tentative incorporation of PG into international medical networks (Sequeira, 1935b).…”
Section: Surveying Sleeping Sickness: Preliminary Resultsmentioning
confidence: 99%
“…The report concluded that the disease was only "lightly endemic" and "apparently benign," with "irregular dissemination across the territory" (Sequeira, 1935a, p.11). It took into account the previous experiences of teams sent by the Escola de Medicina Tropical to study, locate and eradicate trypanosome on the island of Príncipe, where programs had been implemented between 1904and 1913(Amaral, 2008, and later in (Northern) Angola. The fact that the same author published a similar contribution in French illustrates the tentative incorporation of PG into international medical networks (Sequeira, 1935b).…”
Section: Surveying Sleeping Sickness: Preliminary Resultsmentioning
confidence: 99%
“…Em 1887, iniciou-se oficialmente esse ensino na Escola Naval de Lisboa, e, quinze anos mais tarde, o curso foi transferido para a Escola de Medicina Tropical. Como Isabel Amaral (2008) bem explicou, a emergência da medicina tropical portuguesa fez-se em grande medida a partir dessa escola, a par do Hospital Colonial, principalmente da primeira década do século XX em diante.…”
Section: Rui Manuel Pinto Costaunclassified
“…As origens do Instituto de Medicina Tropical de Lisboa, criado em 1935, remontam à antiga Escola de Medicina Tropical -fundada em 1902 para oferecer ensino teórico e prático das chamadas doenças tropicais aos facultativos que se destinassem à Armada e às colônias portuguesas 5 . Porém, o que eram as doenças tropicais?…”
unclassified